GLOBAL PERMIAN TETRAPOD BIOSTRATIGRAPHY AND BIOCHRONOLOGY - Lucas S.G. (My University, 2006)
The most extensive Permian tetrapod (amphibian and reptile) fossil records from the western United States (New Mexico-Texas) and South Africa provide the basis for definition of 10 land-vertebrate faunachrons that encompass Permian time. These are (in ascending order): the Coyotean Seymouran, Mitchellcreekian, Redtankian, Littlecrotonian, Kapteinskraalian, Gamkan, Hoedemakeran, Steilkransian and Platbergian. These faunachrons provide a biochronological framework with which to determine and discuss the age relationships of Permian tetrapod faunas. Their correlation to the marine time scale and its numencal calibrations indicate that the Coyotean is a relatively long time interval of about 20 Ma, whereas most of the other faunachrons are much shorter, about 1-2 Ma long each. The Platbergian may also be relatively long, 14 Ma, although this is not certain. This suggests slow rates of terrestrial tetrapod faunal turnover during most of the Early Permian and late Middle to Late Permian, but more rapid rates of turnover during the latest Early and most of the Middle Permian, especially during the explosive initial diversification of therapsids. © The Geological Society of London.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская